Artificial neural network-based analysis of ferroptosis-associated molecular subtypes and immunological profiles in abdominal aortic aneurysm - Li, Maohua; Xiao, Shasha; Qin, Qi; Fu, Keyun; Wang, Lunchang; Li, Xin; Li, Jiehua (Frontiers in Immunology, 2026)
BackgroundAbdominal aortic aneurysm (AAA) is a severe vascular disease that can lead to rupture and life-threatening hemorrhage. The role of ferroptosis in AAA pathogenesis remains insufficiently understood. This study aims to investigate the role of ferroptosis in AAA by identifying ferroptosis-associated molecular subtypes and examining their relationship with immunological characteristics using an artificial neural network (ANN) model.MethodsWe analyzed three publicly available datasets (GSE7084, GSE47472, and GSE57691) to identify differentially expressed ferroptosis-related genes (FRGs) and employed consensus clustering to classify AAA samples into two subtypes. Immune infiltration was assessed with the CIBERSORT algorithm, and a diagnostic artificial neural network (ANN) model based on subtype-specific genes was developed to discriminate ferroptosis-associated molecular subtypes and derive the NeuraAAA score.ResultsNine differentially expressed FRGs were identified, and the model incorporated three key genes (oncostatin M, heme oxygenase-1, and interleukin-6), achieving high diagnostic accuracy (AUC = 0.988). Consensus clustering stratified AAA samples into two ferroptosis-associated subtypes with distinct immune profiles, with the C1 subtype showing higher immune infiltration and immune scores than C2. The derived NeuraAAA score was elevated in the immune-enriched subtype and correlated with immune-cell infiltration, and a nomogram integrating NeuraAAA and immune score showed good calibration. Immunofluorescence confirmed increased expression of all three genes in AAA specimens.ConclusionOur study reveals the heterogeneous role of ferroptosis in AAA pathogenesis, demonstrating that ferroptosis-associated subtypes are linked to variations in the immune microenvironment. These findings provide new insights into AAA pathophysiology and suggest potential targets for subtype-specific therapeutic strategies, contributing to advances in precision medicine for AAA treatment.